Correlation and path coefficient analyses for some yield-related traits in apple (Malus domestica Borkh) under mid-hill conditions of Himachal Pradesh, India - Praveen Verma1*, Nirmla Chauhan2 and Suman Bodh1 (Electronic Journal of Plant Breeding, 2024)
To understand the utility of genotypes in the breeding program in mid-hill environments of the north-western Himalayas of India, apple cultivars were studied during 2019 and 2020 to discover inter-relationships of variables as well as to study genetic variation across yield attribution traits. For fruit set, fruit drop and fruit volume, high heritability and moderate genetic gain was observed. Substantial correlation between fruit yield per plant and pruning weight, tree volume, tree spread and TSS was observed. However, the increments in tree height and trunk girth were strongly and adversely linked with fruit yield per plant. Thus the traits tree spread, tree volume and flowering length may be used as selection indicators for increased production with high-quality apple cultivars.